ISRN signal processing - International Scholarly Research Network (Cairo, Egypt : Hindawi Pub. Corp., 2011)
"A peer-reviewed, open access journal that publishes original research articles as well as review articles in all areas of signal processing."
Description based on: 2011; title from website (viewed Dec. 14, 2012).
Latest issue consulted: 2011 (viewed Dec. 14, 2012).
Keywords: Signal processing -- Periodicals; Signal processing; Telecommunications; Electronic journals